Relationship between hyperandrogenism, obesity, inflammation and polycystic ovary syndrome. (1st September 2016) - Nehir Aytan, Asli; Bastu, Ercan; Demiral, Irem; Bulut, Huri; Dogan, Murat; Buyru, Faruk
Abstract: This prospective study aimed to determine the status of circulating levels of C-reactive protein (CRP), tumor necrosis factor α (TNF-α), IL-27, IL-35, IL-37, α-1 acid glycoprotein in patients with polycystic ovary syndrome (PCOS) compared with controls and to evaluate their relation with hyperandrogenism and obesity. Forty-eight patients with PCOS (29 obese, 19 lean) and 40 healthy controls (20 obese, 20 lean) were enrolled. CRP, TNF-α, IL-27, IL-35, IL-37, α-1 acid glycoprotein, sex hormone-binding globulin (SHBG), dehydroepiandrosterone sulfate (DHEA-S) levels were measured. Levels of total testosterone, A4, DHEA-S were significantly higher in patients with PCOS than in controls both in the obese and lean groups, while levels of SHBG were significantly lower in all patients with PCOS than in all ( p < 0.05). Free androgen index (FAI) values were significantly higher in all patients with PCOS than in all controls (all p < 0.05). Levels of CRP, TNF-α, α-1 acid glycoprotein were significantly increased in all patients with PCOS compared with all controls (all p < 0.001). FAI had a positive correlation with CRP, TNF-α, α-1 acid glycoprotein, a negative correlation with IL-27, IL-25, IL-37 (all p < 0.01). Body mass index had a negative correlation with IL-27, IL-35, IL-37, a positive correlation with α-1 acid glycoprotein, FAI ( p < 0.05). The findings confirm the proinflammatory state of PCOS. Moreover, obesity along with PCOS significantly elevates the inflammatory status and hyperandrogenism.